The Influence Of Moral Character and Ethical Awareness of Internal Auditor Toward Internal Audit Effectiveness with Whistleblowing System as Moderating Variable - Betri, B; Murwaningsih, Etty (Universitas Muhammadiyah Surakarta, 2021)
This research was to determine how the influence of Moral Character and Ethical Awareness of Internal Auditor withWhistleblowing System Implementation as moderating variable (Empiricial Study of Non Bank State-Owned Enterprises in Palembang). This study was associative research. The research datatype was primary and secondary data. The Population in this study was the internal auditor in the Non-Bank State-Owned Enterprise in Palembang as 35 respondents. The data collection techniques used in this research were questionnaire and interview. Data analysis method in this research was the quantitative analysis. The resultshowed thatMoral character did not gave an influence on Effectiveness of Internal Audit, Effectiveness of In-ternal Audit was significantly and positive influenced by the Ethical Awareness, and Whistleblowing System Implementation quasi moderated Moral Character on Effectiveness of Internal Audit andWhistleblowing System Implementation did not moderated Ethical Awareness of Internal Auditorson Effectiveness of Internal Audit.